Edukasi Pengelolaan Ekowisata Berbasis Manajemen Risiko Di Mempawah Mangrove Park - Heniwati, Elok; Haryono, Haryono; M. Helmi, Syarif; Noviarty, Helisa; Fitriana Hamsyi, Nur (Universitas Nusantara PGRI Kediri, 2023)
Mempawah Mangrove Park is one ecotourism located in Pasir Village, Mempawah Hilir District, Mempawah Regency, West Kalimantan. During the pandemic, mangrove-based tourism was closed, so there were no tourist visits. As a result, no income can be used to manage ecotourism. On the other hand, the level of abrasion around the mangrove area is relatively elevated. For this reason, community service activities (PKM) aim to achieve two purposes, namely 1) providing counseling on risk management of mangrove natural resource asset management and 2) planting mangrove seedlings for ecotourism sustainability and the local environment from potential seawater abrasion. It is expected that through this activity, the understanding of the mangrove community regarding the risks of managing natural resource assets will increase so that they can sustainably develop ecotourism potential.